2014
DOI: 10.1136/sextrans-2013-051410
|View full text |Cite
|
Sign up to set email alerts
|

Is confirmatory testing of Rochecobas4800 CT/NG testNeisseria gonorrhoeaepositive samples required? Comparison of the Rochecobas4800 CT/NG test with anopa/papduplex assay for the detection ofN gonorrhoeae

Abstract: Molecular tests could be used for culture confirmation where available. Roche cobas 4800 Chlamydia trachomatis/Neisseria gonorrhoeae (CT/NG)CT/NG gonorrhoea diagnosis is superior to culture with urogenital and rectal positives not requiring confirmation. Roche cobas 4800 oropharyngeal NG detection findings warrant further prospective study of routine confirmatory testing accounting for its cost and clinical usefulness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 23 publications
3
8
0
Order By: Relevance
“…Previous studies have shown that the dual NAAT for chlamydia and gonorrhoea has high sensitivity and specificity, and does not require further confirmatory testing; 17 , 18 however, this recommendation is only valid in high‐prevalence populations. The Australian Public Health Laboratory Network guidelines recommend that cases identified by NAAT should be confirmed by supplementary testing in low‐prevalence populations, or the PPV of the test should exceed 90% 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the dual NAAT for chlamydia and gonorrhoea has high sensitivity and specificity, and does not require further confirmatory testing; 17 , 18 however, this recommendation is only valid in high‐prevalence populations. The Australian Public Health Laboratory Network guidelines recommend that cases identified by NAAT should be confirmed by supplementary testing in low‐prevalence populations, or the PPV of the test should exceed 90% 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Overall agreement between screening versus confirmatory assay. Overall, the confirmatory assay was positive in 12 Abbott assay, 84.0% (95% CI, 82.2 to 85.6) with the Roche assay, and 65.9% (95% CI, 63.7 to 68.1) with the BD assay ( Table 2). Table 3 shows level of confirmation by each assay, with the screening and confirmatory assay according to sex, sampling year, validation status of sample, and specific sample type.…”
Section: Resultsmentioning
confidence: 99%
“…Perry et al, 1 using a robust confirmatory strategy, have demonstrated that the Cobas 4800 NG test has a high specificity and, in their cohort, positive predicative value (PPV) of >90% and 88.6% for rectal and oropharyngeal swabs, respectively. In spite of local validation work, the proportion of confirmed rectal and pharyngeal results was much lower with our confirmatory strategy.…”
mentioning
confidence: 99%
“…We read with interest the paper by Perry et al 1 as we have just reviewed the performance of our own Neisseria gonorrhoea confirmatory testing strategy. We confirm extragenital samples positive for N. gonorrhoeae on the Cobas 4800NG using the CE-marked Duplicα real-time 2nd generation detection kit (Euroclone diagnostics).…”
mentioning
confidence: 99%